Dietary tea polyphenols ameliorate metabolic syndrome and memory impairment via circadian clock related mechanisms. (July 2017) - Qi, Guoyuan; Mi, Yashi; Liu, Zhigang; Fan, Rong; Qiao, Qinglian; Sun, Yali; Ren, Bo; Liu, Xuebo
Highlights: Tea polyphenols can modulate oscillations of circadian clock genes transcription. Tea polyphenols alleviate metabolic syndrome via circadian clock related mechanisms. Tea polyphenols prevent memory impairment by reprograming circadian clock. Abstract: SCOPE: Circadian rhythms allow organisms to anticipate and exploit daily environmental changes, and food components can adjust internal rhythms in peripheral tissues or even suprachiasmatic nucleus. Dysregulation of circadian rhythms is associated with many pathological conditions. The aim of the current study is to determine potential effects of tea polyphenols on modulating circadian rhythms regarding ameliorating diabetes, metabolic syndrome, and memory disorders. Results: Results demonstrated that tea polyphenols can reverse the relatively shallow daily oscillations of circadian clock genes transcription and protein expression in both liver and hypothalamus triggered by constant darkness. These compounds also alleviate insulin resistance and disorder of glucose/lipid metabolism in constant darkness-treated mice. Concomitantly, tea polyphenols prevented constant darkness-induced memory impairment by inhibiting neuron damage and elevating the expression of neurotropic factor related genes. Conclusion: Tea polyphenols supplementation might serve as future strategies to combat obesity, metabolic syndrome and cognitive disorder induced by circadian dysfunction.